Um estudo sobre os estágios de adoção do CPC PME sob a óptica da teoria institucional - Favarin, Matheus Carlo (2012)
The present study aimed to analyze the present stage of institutionalization of the CPC PME by the small and medium enterprises, from the perspective of the Institutions Theory, taking basis the institutionalization stages developed by Tolbert and Zucker (1999). Through a formative construct, it was sought to measure the level of institutionalization of the CPC PME in small and medium enterprises. In order to conduct the empirical research, questionnaires were sent to 1.786 companies from various sectors, which had up to 500 employees, established, mostly, in the region of the state of São Paulo. Among the valid responses, 20 questionnaires had been properly filled. The data was statistically analyzed by descriptive statistics and ANOVA application. The results showed that small and medium size enterprises in Brazil, according to the analyzed sample, are currently concentrated in the institutional habitualization stage, to the extent that there is not a theory of new structures, as well as the adopters are homogeneous. Another key aspect revealed refers to the knowledge level that the respondents held on the subject (CPC PME). The research found that companies adopting the new accounting practices held a high level of knowledge about the structure in comparison with other companies. Such characteristics can be observed, according Tolbert and Zucker (1999), in the institutional habitualization stage. Among the institutional factors that motivate and inhibit the CPC PME adoption, it was found that the legal aspect stand out as the main motivational factor which conducts the company to the CPC PME adoption. The empirical results of this study were presented to two representatives of professional bodies: CRC SP and SESCON-SP, both in Campinas, in order to deepen the discussion. These representatives gave their opinion regarding the number of companies adopting the CPC PME, the organizational characteristics of the small and medium enterprises and the factors that motivate or inhibit the adoption of new accounting practices. In summary, although it is believed that the accounting professional is endowed with consciousness and applied in carrying out their profession, the empirical research shows that accounting rules have not been applied in small and medium enterprises. The reality of the profession has changed: instead of rules, attention to the essence, the managerial vocation and the management. This attributes, without doubt, greater responsibility to the accounting professional and requires a proactive stance. However, the CPC PME is in place for two years and, since few companies have adopted the new practices so far, it is essential that the attitude of the accountants is evaluated.